Percep????o de farmac??uticos e graduandos sobre o curso de farm??cia e a inser????o no mercado farmac??utico na grande S??o Paulo - Ara??jo, Ana Lu??za Lima (2016)
The number of Higher Education Institutions (HEIs) and the offer of undergraduate courses have grown in Brazil. The pharmaceutical market contemplates wide action in areas as drugstores, pharmacies, hospital pharmacies, pharmaceutical industries, food industries, research, clinical pharmacy, and clinical analysis, among others. The curriculum guidelines for pharmaceutical education demand students are trained to work in all areas of their profession. The aim of this study were research which are the opportunities and working fields for pharmacists in the market in S??o Paulo, until two years after the conclusion of the course of pharmacy, and what are the students??? perception about their future insertion or perspective of the labor market. The results show that the area that absorbed the most of the graduates was drugstore (32,4%), despite only 12,5% of students are willing to be included in this area. The insertion speed at the labor market was considered fast, in until six months, by around 60% of the pharmacists and it is expected to be fast by around 80% of the students. The pharmaceutical area is one of the few that keeps growing even during Brazilian economic and political crisis period.